Challenges and Prospects of the Criminal Justice System in Handling Child Victims and Alleged Offenders in Ethiopia. (February 2021) - Eyasu, Nahom; Haile, Sisay; Tesfaye, Yosef
The current study aims to explore the challenges and prospects of the criminal justice system in handling child victims and alleged offenders in Bahir Dar metropolitan city, North West Ethiopia. A qualitative research design was adopted to achieve this goal. Primary data was collected through semi-structured interviews conducted with victimized children ( n = 25) and in-depth interviews conducted with key informants ( n = 15). Data were analyzed using inductive thematic analysis. The general emergent theme— encumbrance and motivation reflected the challenges and opportunities of the criminal justice system in handling child victims and alleged offenders, respectively. The results from the study revealed that the absence of child-friendly police stations, limited overall assessments and psychosocial supports for child victims, slow, tardy and insensitive justice process, and legal system gaps were critical issues at the initial police contact, investigation, and trial stages of the criminal justice system. It appears from this study that the wellbeing and support needs of victims and witnesses are not yet being adequately addressed. In this study, a major challenge identified was the deficit of law enforcement in the criminal justice system as to the detection and investigation of a crime involving child victims. On the other hand, the initiatives to introduce child protection units and child-friendly police stations, provision of support and assistance, and awareness-raising about child-friendly practices among the criminal justice system are the major prospects that have been taken place within the criminal justice system.